1986
DOI: 10.1111/j.1460-2466.1986.tb01437.x
|View full text |Cite
|
Sign up to set email alerts
|

The “Lead-in” Strategy for Prime-Time Tv: Does It Increase the Audience?

Abstract: An examination of all network prime-time television series aired from 1963 through 1985 shows that a strong lead-in does increase the audience share, especially when the program is neu: or of the same type as the preceding one, or tohen there are fewer viewing alternatives. Of the 963 new prime-time series aired during the 1963-1984 TV seasons b y the three major U.S. commercial television networks, 635 (66 percent) were caricellecl prior to the second season.' In recent years, both the number of new series of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 18 publications
0
20
0
2
Order By: Relevance
“…Earlier studies of inheritance consistently found that the number of program choices-that is, the number of opportunities to "jump ship" for a newly beginning program-was a better predictor of inheritance than similarity of program type (Davis & Walker, 1990;Tiedge & Ksobiech, 1986;Walker, 1988;Webster, 1985). That seems to have changed.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Earlier studies of inheritance consistently found that the number of program choices-that is, the number of opportunities to "jump ship" for a newly beginning program-was a better predictor of inheritance than similarity of program type (Davis & Walker, 1990;Tiedge & Ksobiech, 1986;Walker, 1988;Webster, 1985). That seems to have changed.…”
Section: Discussionmentioning
confidence: 93%
“…There is simply no evidence that higher correlations are associated with higher levels of duplication. Studies of share maintenance or lead-in effects that feature this approach (e.g., Davis & Walker, 1990;McDowell & Dick, 2003;Tiedge & Ksobiech, 1986) certainly drive home the point that lead-in ratings are a powerful determinant of lead-out ratings. In addition, it appears that relationship is enhanced by factors known to affect inheritance (i.e., number of choices and program type).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The weekly Nielsen Station Indices were consulted in order to track viewing changes for the month immediately before and after the January 1, 1989 affiliation switches. Share data for each day were combined and a mean audience size was calculated (Tiedge & Ksobiech, 1986). Chi-square was used to test the significance of changes in household shares for the month immediately preceding the affiliation switches (December, 1988) and the month immediately following the changes (January, 1989)."…”
Section: Research Hypothesesmentioning
confidence: 99%